(untitled) - K.S.SIVAKUMAR (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Introduction: The challenges of the new world order calls for enhancing the appropriate skill-set of individuals. As individuals cannot change the external challenges, it is only prudent that they focus their attention on enhancing their intra-personal skills, especially mind-set and emotions. Emotions colors the behavior and functioning of individuals. The control of one?s own emotions and that of others is referred to as emotional intelligence Objective: The purpose is to deliberate on the Bhagavad Gita?s perception of emotional stability and discern its perspectives that may enrich the skill-set of individuals to adequately address the challenges of the new world order. Method: In the process of deducing the perspectives of the Bhagavad Gita, the concept-based paper clearly brings out the state of emotional stability, its benefits and the path-way to achieve the same. Discussion: According to the Bhagavad Gita, a person of emotional stability is one who has complete control of his/her emotions in all situations. It leads to experiencing peace and free from fear. It arises as a consequence of controlling senses, desires, anger and mind. Conclusion: The above discussion highlights that emotional stability is a state of existence, specific and predominantly an intra-personal necessity for the personal development of individuals, thereby positively impacting productivity and effective inter-personal communication in work place and society.